Ke Kelayakan Usahatani Hidroponik Greenhouse - Anak Agung Ayu Ratna Cahyani; Ketut Budi Susrusa; Gede Mekse Korri Arisena; Ary Bakthtiar (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Hydroponics is one of the profitable business opportunities. However, the main obstacle is that it requires large capital, so the purpose of this study is to determine the inventory of hydroponic farming and analyze the feasibility of greenhouse hydroponic farming. Carried out in Malang Raya with Purposive location determination, for sample determination using accidental sampling from a total sample of 15 respondents, only 9 respondents who have the criteria to analyze the feasibility of farming, this study uses descriptive quantitative data. The 9 respondents were divided into 2 planting patterns, namely monoculture and polyculture. The results of this study, for the inventory of tools and materials adapted to the type of system used and for the non-financial feasibility analysis stated that hydroponic farming is feasible to run from the aspects of market and marketing, technical and social. In terms of management, it is not feasible to run. From a financial point of view with a farming age of 3 years and for the interest rate used of 3%, the results show that in terms of Net B / C Ratio investment criteria from 9 respondents there is 1 monoculture farm that is feasible to run and 3 polyculture farms that are feasible to run. As for the NPV value of 9 respondents there are 2 polyculture farms that are not feasible. And for the results of the IRR analysis states that the 9 ponds are not feasible to run.